INTERACTIONS BETWEEN LASER BEAM AND ORAL TISSUES DURING LASER-ASSISTED SURGICAL PROCEDURES - Agop-Forna Doriana; Vasincu Decebal; Topoliceanu Claudiu; Ţarevici Eugenia Larisa; Ţibeica Silviu Catalin; Ursu Marius Octavian; Giuvara Constantin Razvan; Ciurcanu Oana (Romanian Dental Association for Education, 2020)
The knowledge regarding the mechanisms of the interaction between laser energy and the oral cavity tissues is a major factor in the proper selection of the wavelength, in the optimum setting of parameters as well as in the practical execution of the laser-assisted oral surgical procedures. In oral surgery, the laser energy can interact with the oral tissues in four ways: absorption, reflection, diffusion, transmission. The photobiological effects of laser energy on the oral tissues include the photochemical, photothermal and photomechanical effect, as well as the biostimulation effect. In oral surgery on soft tissues various categories of lasers can be used: diode, erbium (Er :YAG; Er,Cr :YSGG), Nd:YAG and CO2 lasers. The interaction of the laser beam with the oral soft tissues depends on variables such as the pigmentation degree, the water content and tissue thickness. In interventions at the level of the oral bone tissues, only erbium (Er :YAG; Er,Cr :YSGG) and CO2 lasers are recommended. These lasers can be used for resections at the level of the bone tissues due to the photoablation process achieved by photothermal reaction, which transforms the irradiated tissues into gas or plasma combined with a photochemical and photoacoustic effect. The proper use of safety rules during laser-assisted procedures avoid the adverse effects at the level of soft and hard oral tissues.